Piutang Bermasalah dan Keberlanjutan Usaha: Studi Empiris atas Manfaat Ekonomi Anggota Koperasi - Rima Elya Dasuki; Sekar Ayu Milani Prabawati (LPPM Universitas Koperasi Indonesia, 2025)
This study aims to analyze the impact of problem receivables on business sustainability and member benefits at the Indonesian Tofu and Tempeh Producers Cooperative (Koperasi Tahu Tempe Indonesia/KOPTI) in Bandung. The research method used was a case study, collecting primary data through interviews and secondary data from financial reports. The results indicate that problem receivables at KOPTI do not affect business sustainability, as the Non-Performing Loan (NPL) ratio remains below 10%. The cooperative's business sustainability impacts both direct and indirect economic benefits for members. These findings provide important implications for cooperative management to maintain the quality of receivables and business sustainability for the welfare of members.